Beyond the Word Count: Using Assignment Sheets to Promote Genre Awareness - Allen, Kristen (Discourse and Writing/Rédactologie, 2024)
Despite the best efforts of their instructors, first-year students often misinterpret or even ignore assignment sheets, leading to unmet learning outcomes and demoralising marks. Like academic writing as a whole, assignment sheets often contain conventions, terminology, and expectations that are unfamiliar to incoming undergraduates. In this paper, I propose an activity which calls students’ attention to assignment sheets as a genre, helping them meet the practical requirements of their assignment as well as develop their genre awareness. Students work in groups to rank the major goals of their current assignment as specified in the assignment sheet and use previous student responses to consider the diverse ways in which these goals can be fulfilled. Using this exercise, students can discover the close generic and rhetorical connection between the assignment sheet and the written responses it generates, as well as the variety of successful uptakes that are possible within the assigned genre.